Suitability of powerplant disposed water for irrigation of Ashuganj agro-irrigation project in Bangladesh - Rana, MM; Islam, MT; Datta, S; Rahman, MM; Adham, AKM (Progressive Agriculture, 2019)
A study was conducted to analyze the quality of power plant disposed water for irrigation and its impact on the soil of Ashuganj agro-irrigation project in Bangladesh. Water samples were collected during the irrigation period and chemically analyzed for the assessment of their quality based on pH, electrical conductivity (EC), sodium adsorption ratio (SAR), soluble sodium percentage (SSP), residual sodium bicarbonate (RSBC), Kelley‘s ratio (KR), total hardness (TH), magnesium absorption ratio (MAR) and permeability index (PI). Most of the water samples were basically excellent in case of EC and SAR, satisfactory in respect of RSBC and good based on SSP and PI for irrigation use. The relationships between the pairs of KR-SAR, KR-SSP, and SSP-SAR of the water samples were very strong with correlation coefﬁcient around 1. Moreover, the values of pH, EC, Na, K, Ca, Mg and organic carbon of the soil samples were in the suitable range before and after crop cultivation. Therefore, it can be inferred that the power plant disposed water of the agro-irrigation project is suitable for irrigation as well as crop cultivation without any hazard of soil health. Progressive Agriculture 30 (1): 113-124, 2019